The Application of Recovery Strategies in Basketball: A Worldwide Survey - Pernigoni, Marco; Conte, Daniele; Calleja-González, Julio; Boccia, Gennaro; Romagnoli, Marco; Ferioli, Davide (Frontiers in Physiology, 2022)
The purpose of this study was to assess the perceived usefulness, actual use and barriers to the implementation of recovery strategies among basketball practitioners. 107 participants (strength and conditioning coaches, sport scientists, performance specialists) from different countries and competitive levels completed an online survey. Most participants rated recovery strategies as either extremely (46%) or very important (49%). Active recovery, massage, foam rolling, and stretching were perceived as most useful (80, 73, 72 and 59% of participants, respectively) and were most frequently adopted (68, 61, 72 and 67%, respectively). Participants mentioned lack of devices and facilities (51%), excessive cost (51%), lack of time (27%), players’ negative perception (25%) and lack of sufficient evidence (16%) as barriers to the implementation of recovery strategies. The present findings reveal that some dissociation between scientific evidence and perceived effectiveness was present among the study participants. A possible solution would be to ensure that scientific evidence-based guidelines are followed when considering the application of recovery strategies. Regarding actual use, participants favored easily implementable strategies (e.g. active recovery, stretching), rather than evidence-supported, but expensive and/or impractical strategies (e.g. whole-body cryotherapy). Possible solutions may include the use of practical tools that don’t need specific facilities, the development and validation of new low-cost recovery devices, the promotion of players education regarding recovery strategies, and conducting further research to increase the scientific knowledge in the area.